The quality of life in neoadjuvant versus adjuvant therapy of esophageal cancer treatment trial (QUINTETT): Randomized parallel clinical superiority trial. Issue 13 (24th May 2022) - Malthaner, Richard A.; Yu, Edward; Sanatani, Michael; Lewis, Debra; Warner, Andrew; Dar, A. Rashid; Yaremko, Brian P.; Bierer, Joel; Palma, David A.; Fortin, Dalilah; Inculet, Richard I.; Fréchette, Eric; et al.
Abstract: Background: We compared the health‐related quality of life (HRQOL) in patients undergoing trimodality therapy for resectable stage I‐III esophageal cancer. Methods: A total of 96 patients were randomized to standard neoadjuvant cisplatin and 5‐fluorouracil chemotherapy plus radiotherapy (neoadjuvant) followed by surgical resection or adjuvant cisplatin, 5‐fluorouracil, and epirubicin chemotherapy with concurrent extended volume radiotherapy (adjuvant) following surgical resection. Results: There was no significant difference in the functional assessment of cancer therapy‐esophageal (FACT‐E) total scores between arms at 1 year ( p = 0.759) with 36% versus 41% (neoadjuvant vs. adjuvant), respectively, showing an increase of ≥15 points compared to pre‐treatment ( p = 0.638). The HRQOL was significantly inferior at 2 months in the neoadjuvant arm for FACT‐E, European Organization for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ‐OG25), and EuroQol 5‐D‐3 L in the dysphagia, reflux, pain, taste, and coughing domains ( p < 0.05). Half of patients were able to complete the prescribed neoadjuvant arm chemotherapy without modification compared to only 14% in the adjuvant arm ( p < 0.001). Chemotherapy related adverse events of grade ≥2 occurred significantly more frequently in the neoadjuvant arm (100% vs. 69%, p < 0.001). Surgery related adverse events of grade ≥2 were similar in both arms (72% vs. 86%, p = 0.107). There were no 30‐day mortalities and 2% vs. 10% 90‐day mortalities ( p = 0.204). There were no significant differences in either overall survival (OS) (5‐year: 35% vs. 32%, p = 0.409) or disease‐free survival (DFS) (5‐year: 31% vs. 30%, p = 0.710). Conclusion: Trimodality therapy is challenging for patients with resectable esophageal cancer regardless of whether it is given before or after surgery. Newer and less toxic protocols are needed. Abstract : This randomized trial assessed the health related quality of life in esophageal cancer patients undergoing neoadjuvant versus adjuvant trimodality therapy. Every patient experienced at least one adverse event. The quality of life was worse for patients undergoing neoadjuvant compared to adjuvant chemoradiation with no significant difference in either overall survival or disease‐free survival. More effective therapy is needed.